Penatalaksanaan Holistik Laki – Laki Usia 65 Tahun Dengan Gout Arthritis Dan Diabetes Melitus Melalui Pendekatan Kedokteran Keluarga Di Wilayah Kerja Puskesmas Panjang : Laporan Kasus - Muhammad Dzaki Hidayatullah (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2024)
Gout arthritis and diabetes mellitus are chronic diseases that need to be controlled with medication adherence and healthy lifestyle to prevent complications from these diseases. The Riskesdas 2018 show 7,30% and 1,6% of people aged ≥ 15 years with joint disease and diabetes respectively in Indonesia. Aims at implementing holistic and comprehensive family doctor services by identifying risk factors, clinical problems, management and prevention of patient complications based on evidence-based medicine through a patient centered and family approach. This research is included in the case report type. Primary data was collected from autoanamnesis and alloanamnesis, physical and supporting examinations, and home visits. Secondary data was obtained from patient medical records. The basis of the assessment is a holistic diagnosis of the beginning, process and end of the research qualitatively and quantitatively. Patient Mr. Y, 65 years old, has been diagnosed with gout arthritis and diabetes mellitus type 2. The internal factor is ignorance about the cause of the disease. The external factors are family history of the disease and family ignorance about the disease. Pharmacological and non-pharmacological intervention were carried out by education and counselling through family conference. The diagnosis and management of this patient has been carried out in a holistic, patient centered, family approach and refers to a number of theories and the latest research. In the behavior change process, patients and families have reached the adoption stage.